2020
DOI: 10.3390/antiox9121199
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Improves Brain–Gut Axis Inducing Remodeling of Gut Microbiota in DOCA-Salt Hypertensive Rats

Abstract: Microbiota is involved in the host blood pressure (BP) regulation. The immunosuppressive drug mofetil mycophenolate (MMF) ameliorates hypertension. The present study analyzed whether MMF improves dysbiosis in mineralocorticoid-induced hypertension. Male Wistar rats were assigned to three groups: untreated (CTR), deoxycorticosterone acetate (DOCA)-salt, and DOCA treated with MMF for 4 weeks. MMF treatment reduced systolic BP, improved endothelial dysfunction, and reduced oxidative stress and inflammation in aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…We observed that in DOCA-salt animals, the gut microbiota was characterized by a reduced evenness, with no significant changes in F/B ratio and a higher proportion of lactate-producing bacteria, which was accompanied with high levels in plasma lactate. This signature of gut microbiota is consistent with the previous data shown in mice and rats with DOCA-salt hypertension [ 7 , 40 , 41 ]. The manipulation of the gut microbiota with oral antibiotic DOX reduced richness and number of species; however, it did not alter the bacterial load.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We observed that in DOCA-salt animals, the gut microbiota was characterized by a reduced evenness, with no significant changes in F/B ratio and a higher proportion of lactate-producing bacteria, which was accompanied with high levels in plasma lactate. This signature of gut microbiota is consistent with the previous data shown in mice and rats with DOCA-salt hypertension [ 7 , 40 , 41 ]. The manipulation of the gut microbiota with oral antibiotic DOX reduced richness and number of species; however, it did not alter the bacterial load.…”
Section: Discussionsupporting
confidence: 93%
“…DOX treatment decreased lactate-producing bacteria, which also may be correlated with the reduction of plasma lactate levels that could contribute to the beneficial effect to reduce the BP; it has already been detailed that plasma lactate level is linked to increased blood pressure [ 42 , 43 ]. In fact, the decrease in gut lactate-producing bacterial populations by the immunosuppressive drug moletil mycophenolate and consumption of a high-fiber diet with Bifidobacterium breve reduces plasma lactate and hence prevents the rise of blood pressure, attenuation of both renal and cardiac fibrosis and the improvement of endothelial function in DOCA-salt rats [ 7 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased intestinal permeability associated with reduced tight junctional protein expression has been reported in several rodent models of hypertension, including Ang II (angiotensin II)–induced, deoxycorticosterone acetate (DOCA)-salt and spontaneously hypertensive rat (SHR) models. 3,24,25 For example, in SHR, a genetic model of progressive hypertension from 4 weeks of age, lower tight junction protein expression in the gut and increased intestinal permeability, along with enhanced gut sympathetic activity, was observed in adult rats but also young SHR before the onset of hypertension. 3 Similarly, findings of impaired intestinal integrity and increased sympathetic innervation density was demonstrated in the Ang II–induced model of hypertension in adult male Sprague-Dawley rats.…”
Section: Intestinal Dysfunction and Hypertensionmentioning
confidence: 99%
“…Sodium retention in hypertension is associated with the failure of signals to decrease renal sodium transport when sodium intake is greater than what is needed to maintain a normal sodium balance [ 10 , 11 , 12 ]. Normal sodium balance is achieved by proper interactions among several organs, including the kidney, brain, heart, liver, intestines, muscle, skin, and immune system [ 13 , 14 , 15 , 16 , 17 , 18 ]. One of the main factors that maintains a normal sodium balance is the renal-selective action of dopamine produced by the kidney [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%